Ley Lines - Hix, H. L. (Book collections on Project MUSE., 2014)
In This Unique Anthology, working poets respond to questions about their recent books, painters and other artists offer statements about their work, and writers respond to artworks and reflect on the creative process. These offerings and exchanges are juxtaposed so as to speak to one another in a capacious, resonant dialogue, The result is a broad-minded and inclusive poetics, a vision of creative work as a constituent of personal and civic life.